Effect of flaxseed (Linum usitatissimum) and soybean (Glycine max) oils in Egyptian lactating buffalo and cow diets on the milk and soft cheese quality (Acta Scientiarum. Animal Sciences, 2020)
Produce and compare soft cheese with potential benefits of human health from Egyptian buffalo's and cow's milk was studied. Eight Egyptian lactating buffalos and cows were fed a total mixed ration supplemented with either 0% oil (CD), 2% flaxseed oil (DFO), 2% soybean oil (DSO), or 2% of their mixture (1:1, DFSO) according to a double 4 x 4 Latin Square design. Milk yield was similar between buffalo's diets but was higher in cows fed a DFO, DSO or DFSO resulting in 11.15, 8.21% or 8.97% increases compared with the control diet, respectively. Milk composition was not significantly affected in both buffalos and cows fed diets. The DFO, DSO or DFSO displayed decreased short-chain fatty acids, especially DSO and DFSO (3.73 and 3.33%, respectively) when compared to CD for buffalo milk (6.32%). The DSO and DFSO were  more effective for increasing unsaturated fatty acids followed by the DFSO in buffalo's milk fat (42.31 and 41.90 %), whereas DFO and DFSO were more effective in cow's milk fat (39.67 and 39.84%), respectively. DFO, DSO or DFSO had no significant effect on the yield, composition and sensory properties of resultant soft cheese compared to the CD for both lactating cows and buffalos. During storage, a diet rich in unsaturated fatty acids enhances protein proteolysis and antioxidant activity of soft cheese during storage compared to the CD especially for soft cheese produced from buffalo's milk.